Sex differences in the genetics of autism spectrum disorder and their impact on gene expression associated with mitochondrial function - María de los Angeles Carcamo; Rodrigo A. Quintanilla; William Tiznado; Lina M. Ruiz (Mitochondrial Communications, 2024)
Autism spectrum disorder (ASD) is a neurodevelopmental condition that affects social-communicative skills and is characterized by restricted and stereotyped behaviors. It affects more males, with a ratio of 4:1, and has a prevalence of 1:54 children. Manifestations of ASD vary by gender, with specific behaviors less pronounced in females. Using data from the Gene Expression Omnibus repository, this research explored sex-related genetic differences in ASD and their impact on mitochondrial gene expression. Peripheral blood DNA was found to exhibit differential methylation patterns by sex, with additional alterations in individuals with ASD. Sex-specific transcriptional changes were also identified in cord blood from high-risk ASD pregnancies. Of 50 genes with differential methylation by sex, only the PLEKHN1 gene is related to mitochondrial function. Age correlated with symptoms and diagnosis in males, whereas PLEKHN1 methylation was associated with age and internalizing symptoms in females. In conclusion, sex influences genetic contributions in ASD, affecting mitochondrial gene expression.